2021
DOI: 10.1155/2021/6682094
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Headache and Associated Factors in Al-Kharj, Saudi Arabia: A Cross-Sectional Study

Abstract: Background. Only few studies have investigated the prevalence and risk factors of headaches among the Saudi population. The study aimed to estimate the prevalence of headache and to explore its associated risk factors Al-Kharj, Saudi Arabia. Methods. The multistage sampling technique was used to enroll 1200 population-based participants who were asked to complete a self-administered questionnaire about headaches, demographics, and several other parameters such as smoking status and different chronic and psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
4
8
1
Order By: Relevance
“…Among lifestyle and behavioral factors, in addition to smoking, which has been observed in prior studies, work significantly increased the intake of OTC drugs. This result is similar to findings of previous national and international studies, which documented the relationship between these factors and headache [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among lifestyle and behavioral factors, in addition to smoking, which has been observed in prior studies, work significantly increased the intake of OTC drugs. This result is similar to findings of previous national and international studies, which documented the relationship between these factors and headache [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the current descriptive cross-sectional study design, the prevalence of factors associated with the condition was observed using the “prevalence ratio” ( 13 ). To the best of our knowledge, this is the first study on headache epidemiology that has utilized PR as a measure of association other than the odds ratio in a cross-sectional study design ( 22 ). It was found that in the stress group, the prevalence of headaches was high (65%; Figure 6 ), and it is well known that stress has a major influence on headache, and its frequency also when the latter is directly proportional to stress intensity ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within Saudi Arabia, a study conducted in Al-Kharj revealed a 3% prevalence of headaches in the general population, with a higher likelihood among females [ 15 ]. However, the specifics regarding the characteristics of headaches among pregnant women in Saudi Arabia remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%